LL-KNN ACW-NB: Local Learning K-Nearest Neighbor in Absolute Correlation Weighted Naïve Bayes untuk Klasifikasi Data Numerik - Azminuddin I. S. Azis; Budy Santoso; Serwin (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Naïve Bayes (NB) algorithm is still in the top ten of the Data Mining algorithms because of it is simplicity, efficiency, and performance. To handle classification on numerical data, the Gaussian distribution and kernel approach can be applied to NB (GNB and KNB). However, in the process of NB classifying, attributes are considered independent, even though the assumption is not always right in many cases. Absolute Correlation Coefficient can determine correlations between attributes and work on numerical attributes, so that it can be applied for attribute weighting to GNB (ACW-NB). Furthermore, because performance of NB does not increase in large datasets, so ACW-NB can be a classifier in the local learning model, where other classification methods, such as K-Nearest Neighbor (K-NN) which are very well known in local learning can be used to obtain sub-dataset in the ACW-NB training. To reduction of noise/bias, then missing value replacement and data normalization can also be applied. This proposed method is termed "LL-KNN ACW-NB (Local Learning K-Nearest Neighbor in Absolute Correlation Weighted Naïve Bayes)," with the objective to improve the performance of NB (GNB and KNB) in handling classification on numerical data. The results of this study indicate that the LL-KNN ACW-NB is able to improve the performance of NB, with an average accuracy of 91,48%, 1,92% better than GNB and 2,86% better than KNB.